Intramuscular myxoma of a thigh: A case report - Terzić, Zoran; Vukčević, Batrić; Paunović, Marinko; Djordjević, Boban; Terzić, Stojan (Vojnosanitetski pregled, 2021)
Introduction. Myxoid lesions may present as benign, locally invasive, or malignant tumors. The incidence of intramuscular myxoma is nearly 1 case in 1,000,000 inhabitants. Case report. A 73-year-old man presented to our clinic with a painless, subcutaneous tumor of the adductor region of the left thigh. Computed tomography and magnetic resonance imaging showed a cystic tumor with thin septae located in the adductor muscles. The tumor was extirpated in toto, with the histopathological confirmation of an intramuscular myxoma. Conclusion. This example may serve to increase the awareness of a successful intramuscular myxoma treatment among surgeons and radiologists in small countries.